Semiotic of Heartbreak: A Roland Barthes Analysis of Luka Dalam Lyrics by Manja Mooy - Aran, Maria Trifonia Teniba; Setyowati, Endang; Muliyono , Nurwakhid (Journey: Journal of English Language and Pedagogy, 2026)
This study analyzes the meaning of the lyrics of Manja Mooy's song "Luka Dalam" using Roland Barthes's semiotic framework. This study aims to identify and interpret the denotative, connotative, and mythological meanings embedded in the lyrics. Using a qualitative descriptive-interpretive approach focused on pure text analysis (content analysis), the data consists of words, phrases, clauses, and stanzas taken from the song lyrics as the primary source without involving field data triangulation. Data were collected through documentation, listening, and note-taking techniques, then analyzed through Barthes's three levels of signification: denotation, connotation, and myth. The findings show that at the denotative level, the lyrics explicitly depict emotional pain and betrayal. At the connotative level, the lyrics represent deep psychological wounds and the loss of trust. Meanwhile, at the mythic level, the song constructs a cultural narrative about the moral consequences of infidelity and reinforces social values regarding emotional responsibility. The novelty of this study lies in revealing the myth of 'emotional resilience' in modern pop song lyrics, which shows a shift from merely passive grief narratives to moral assertiveness towards betrayal. Through this analysis, the research shows that song lyrics function as cultural texts with layered ideological messages, as well as providing a practical contribution in increasing listeners' appreciation of the symbolic meaning of popular music.